Trade unions and the right to strike ;Comparative socio - legal study in labour - management relations - Dhyani, S.N. (Delhi, 1978)
The present study on Trade Unions and Strikes' is a critical and evaluative assessment of the existing labour-manage ment relations of India. Trade unions in India have grown up without a sound trade union philosophy. There has been over emphasis on industrial development without sound trade union development. It has led to lopsided development of trade unions and indiscriminate use of strikes and other forms of industrial conflicts even though there are numerous laws, codes, resolutions and understandings which restrict, regulate, control and even prohibit strikes. This study, therefore, pro poses to examine some of the important areas of labour management relations in India and elsewhere. A compara tive study of labour-management relations framework and public policy of U.S.A., U.K. and other developed countries has been made for the benefit of our planners and policy makers. Thus it is a comparative socio-legal study of trade unions, legal basis of right to strike, industrial relations machi nery and other state regulatory processes, voluntary choice processes including collective bargaining, voluntary arbitration etc., of U.S.A., U.K., Germany and other countries with special reference to India. It is with this view that the ex perience of other countries in the field of labour-management relations might be useful in bringing about the necessary changes in the patterns and perspectives of existing labour management problems in India.
Keywords: Trade - unions - India